Project Based Chemistry Learning on the Topic of Making Biodegradable Film from Corn Cobs: A Qualitative Content Analysis - Naila Azizah; Asep Supriatna; Triannisa Rahmawati (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Plastic waste has brought us an enormous environmental challenge. One solution that could be done to solve the problem of plastic waste is to switch to ordinary plastic using biodegradable film. Corn cob is a type of lignocellulosic waste. And it could be used as biodegradable film material. This research aims to construct a Teaching-Learning Sequence (TLS) in film formation from corn cobs. The Teaching-Learning Sequences (TLS) that were designed can be made into lesson plans or learning materials with the Project-Based Learning (PjBL) model that fits with the "Projek Penguatan Profil Pelajar Pancasila (P5)" program in the current curriculum in Indonesia. This research is based on qualitative content analysis. It has four stages: collecting material, making a descriptive analysis, selecting categories, and evaluating. Data analysis and validation through experts were used. These validators included two experienced chemistry teachers and two chemistry education lecturers. Therefore, the validated Teaching-Learning Sequence (TLS) applies to learning activities. The discussion is split into four points: the first is the rate of plastic waste, the second is what corncobs consist of and their potential, the third is the process of creating biodegradable film, and the fourth point is the advantage of converting corncob waste to biodegradable film.